2019
DOI: 10.4102/sajesbm.v11i1.291
|View full text |Cite
|
Sign up to set email alerts
|

The structural validity of the innovative work behaviour questionnaire: Comparing competing factorial models

Abstract: Understanding and building theory on innovative work behaviour (IWB), as well as the parallel measurement thereof, is a prerequisite to the development of models for enhancing IWB. Most theorists propose IWB as a sequential process involving steps such as exploration, generativity, investigation, championing and application. These steps are also reflected in the design of IWB measurements. In this study, the theorised step-structure of IWB, as proposed by Kleysen and Street in 2001, is tested -relying on gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In their studies, Messmann and Mulder (2011) have recommended constructing “additional items for idea realization” (p. 57). Steyn and Bruin (2019) discuss that idea exploration scores highest among the other constructs (p. 8). According to De Jong and Den Hartog (2010), who have explored idea exploration, generation, championing and implementation communicate that “evidence of the distinctiveness of the four dimensions was weak” (p. 33).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In their studies, Messmann and Mulder (2011) have recommended constructing “additional items for idea realization” (p. 57). Steyn and Bruin (2019) discuss that idea exploration scores highest among the other constructs (p. 8). According to De Jong and Den Hartog (2010), who have explored idea exploration, generation, championing and implementation communicate that “evidence of the distinctiveness of the four dimensions was weak” (p. 33).…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, IWB has gained popularity among many authors in different fields. For instance, Steyn and Bruin (2019) present a “detailed conceptualization of the complex concept of IWB” while also “exposing the structure of IWB.” Noteworthy, too, Messmann and Mulder (2012) claim that “reflection related to the improvement of competence and performance may be a consequence of IWB” (p. 58). Moreover, Carmeli et al (2006) and Noefer et al (2009) have mentioned that IWB appears when an employee identifies problems or challenges at work and attempts to propose new solutions for those problems or challenges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although empirical support for the theorised structure was mixed, Kleysen and Street (2001) suggest the use of the items as a single measure of innovation behaviour, as did Hebenstreit (2003). Steyn and De Bruin (2019) were able to replicate the five-factor structure of IWB as proposed by Kleysen and Street. Steyn and De Bruin (2020) also demonstrated that the measure was invariant across gender (equal latent means invariance; CFI = 0.973 and RMSEA = 0.057) and report alphas coefficients of 0.947 (men) and 0.954 (women).…”
Section: Measurement Instrumentsmentioning
confidence: 78%